KOMUNIKASI RITUAL DALAM UPACARA TAWUR LABUH GENTUH DI TAMAN MAYURA KOTA MATARAM - Asmara Putra, I Nyoman Buda (Widya Duta: Jurnal Ilmiah Ilmu Agama dan Ilmu Sosial Budaya, 2021)
Communication is a fundamental need in human life. By communicating, humans interact with God, fellow humans and the natural environment to establish a harmonious life. Hindus in West Nusa Tenggara carry out a tawur labuh gentuh ceremony at Mayura Park, Mataram City implementing the tri hita karana concept. In the process of implementing the tawur labuh gentuh ceremony, communication dynamics occur using symbols that need to be understood together. This study, entitled "Ritual Communication in the Tawur Labuh Gentuh Ceremony in Mayura Park, Mataram City", raises the issue, namely how is the form of ritual communication in the tawur labuh gentuh ceremony in Mayura Park, Mataram City? The general purpose of this research is to broaden scientific insight about ritual communication and provide explanations to various parties regarding the tawur labuh gentuh ceremony so that it can be socialized to the public and to religious institutions in making a policy. Its specific purpose is to describe and analyze the form of ritual communication in the tawur labuh gentuh ceremony in Mayura Park, Mataram City.This research was conducted using qualitative methods, so that the data analysis was carried out in a descriptive qualitative and interpretative manner. Mayura Park, Mataram City, West Nusa Tenggara Province was chosen as the research location because the tawur labuh gentuh ceremony was held in a large degree for the first time in this place. Besides that, the limited information makes Hindus not all know the procession and the meaning of the ceremony from beginning to end, so it is deemed necessary to conduct research as a reference source. This form of ritual communication in the tawur labuh gentuh ceremony combines two theories used as a scalpel, namely Jurgen Habermas Communicative Action Theory and Charles Sander Pierce's Theory of Communication Semiotics.